Factors Associated with Pulmonary Embolism Recurrence and the Benefits of Long-term Anticoagulant Therapy - Sanchez, Francisco J.A.; Martínez, Jose L.A.; Echezarreta, Mirem A.U.; Garcia, Ione V.; Alvaro, Jorge R. (Cardiovascular & Haematological Disorders - Drug Targets, 2017)
Background: Venous thromboemboli tend to recur. However, the causative factors underlying pulmonary embolism recurrence are not well defined. Aims: To explore the factors associated with pulmonary embolism recurrence. Patients and Methods: Patients diagnosed with pulmonary emboli between 2004 and 2013 at our institution were enrolled. Duration of anticoagulant therapy, new episodes of venous thromboembolism, and deaths were recorded. Results: Pulmonary embolism was diagnosed in 528 patients (median age: 76 years, interquartile range [IQR]: 16; male: 45%). The median follow-up time was 34 months (IQR: 52). In total, 477 patients completed ≥3 months of anticoagulation therapy. Permanent anticoagulation was indicated in 217 (45%) patients, and therapy was discontinued in 260 (55%) patients. Overall, 79 patients experienced a recurrence (5.6 per patient-year). Recurrence was significantly associated with anticoagulation discontinuation (4% vs. 27% of patients who maintained or discontinued therapy, respectively; P<0.001; 95% confidence interval -0.95, -0.86). The median duration between anticoagulation withdrawal and recurrence was 6.5 months (IQR: 23.25). Factors associated with recurrence were unprovoked pulmonary embolism (odds ratio [OR]: 0.45), a greater degree of pulmonary arterial obstruction (OR: 2.5), a delay in initiation of anticoagulation (OR: 3), and higher plasma D-dimer levels during treatment (OR: 2.3). Survival rates were improved for patients who maintained anticoagulation therapy relative to those who discontinued. Conclusion: Pulmonary embolism has a high recurrence rate. Permanent anticoagulant therapy should be considered for patients with idiopathic pulmonary embolism, a high thrombotic burden, and persistently elevated D-dimer levels during treatment, and for patients where therapy was initially delayed.
Keywords: pulmonary embolism